Relationship of Cognitive Style and Job Level: First Demonstration of Cultural Differences - Kageyama, Tetsuya; Sugiura, Motoaki (Frontiers in Psychology, 2017)
Higher-level managers are said to have a more intuitive cognitive style. To verify this hypothesis, we must consider three factors that have often been left out of account. Previous studies, related to managerial cognitive style and job level, used a unidimensional model of cognitive style, did not consider age, and have mainly been conducted in the UK. Our study replicated previous studies on a population of 1,533 Japanese fulltime workers, using a questionnaire based on a two-dimensional model of cognitive style and setting a frame by age for each job level. Our results showed that higher job levels are associated with more rational cognitive styles. There were significant main effects of the interaction of job level and job level by age in rational thinking style. There was no correlation between intuition and job level. Our findings are the first demonstration that the relationship between job level and cognitive style likely depends on culture.